Production of mint whey drink at private and collective farms and agricultural holdings. Issue 1 (November 2020) - Larionov, G; Semenov, V; Lavrentyev, A; Sherne, V; Kayukova, O; Mardaryeva, N; Ivanova, R
Abstract: This research aimed the development production of prophylactic whey drinks which allows enhancing the efficient use of resources of high-value dairy byproducts including cheese and curd whey. High level of safety and quality of milk supplied, soft, semi-hard cheeses and dry-curd cottage cheese, as well as curd whey were adapted. Pepper mint was added as a source of extra vitamins, mineral salts, macro- and micronutrients, dietary supplements. The first recipe for a whey drink with the addition of mint syrup includes curd whey 1 L, mint 1 g, sugar 30 g, water 25 mL, citric acid 4 g. The second recipe differs from the first in that peppermint contains 2 g, the third recipe for mint contains 3 g. The amount of whey, sugar and citric acid in the second and third recipes corresponds to the first recipe. Plant-based components of whey drink act as analeptics and expand the assortment. Also, the research aimed to develop zero waste and low waste technology for private and collective farms and agricultural holdings and as a result, provide the solution to whey disposal issue.